A novel grid-stiffening concept for locally reinforcing window openings of composite fuselage panels using streamline stiffeners. (October 2022) - Alhajahmad, Ahmad; Mittelstedt, Christian
Abstract: Streamlines are smooth and continuous curves that naturally never intersect with each other and fit the shape of the body that exists in an ideal fluid flow. These features can be exploited to employ the streamlines as reference trajectories for stiffening panels with cutouts. Moreover, the streamline stiffeners can properly be placed to locally reinforce the cutouts leading to integrated curvilinear grid-stiffening concepts that can be implemented in composite fuselage panels with window openings. In this paper, based on this new concept, the buckling performance of grid-stiffened fuselage panels with reinforced window openings is addressed. Two common shapes of commercial aircraft fuselage windows are considered. Grid-stiffened panels with different grid patterns subjected to in-plane uniaxial and biaxial compressive loads are investigated. Analysis and design optimization studies are conducted. In the optimization study, a panel with streamline fibres and stiffeners is considered where the layup of the skin is optimized for maximum buckling load. The buckling performance of the panels with streamline fibres and stiffeners constructed based on the proposed concept is compared with that obtained for traditional panels with straight fibres and stiffeners. It is shown that the proposed grid-stiffening concept offers substantial improvements in the buckling capacity compared with the conventional grid-stiffening approach baseline. Highlights: A novel grid-stiffening concept is proposed for reinforcing fuselage window openings. Trajectories of the fibres and stiffeners are defined using streamlines of fluid flow. Buckling capacity of grid-stiffened fuselage panels with reinforced window openings is studied. Stacking sequence of skins is optimized for maximum buckling load using streamline fibres. The proposed concept offers substantial improvements in the buckling performance.